2020
DOI: 10.1515/jpem-2019-0119
|View full text |Cite
|
Sign up to set email alerts
|

BMI relationship to the onset of puberty: assessment of growth parameters and sexual maturity changes in Egyptian children and adolescents of both sexes

Abstract: BackgroundPuberty is the period of human growth and development. To determine the onset of puberty with regards to the effect of higher adiposity, together with growth parameters of the participants at various stages of sexual maturity for both sexes.MethodsThe study was conducted on 1944 children (8–16) years; 1022 girls (52.6%) and 922 boys (47.4%) were taken at random. Pubertal assessment was done using Tanner staging that assigned breast development in females and pubic and axillary hair in males and femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 22 publications
1
13
0
1
Order By: Relevance
“…In this sense, it has been shown that the prevalence of vitamin D deficiency increases among older children [39,40], and puberty seems to influence this deficiency [4,41], probably due to the increased requirement of vitamin D for growth and bone turnover [14]. It is worth noting that puberty is marked by an increase in body weight, which is associated with IR and a reduction in serum 25(OH)D levels [17,[41][42][43]. However, previous studies found no associations between serum 25(OH)D and insulin parameters in prepubertal children [38,42].…”
Section: Puberty Insulin Resistance and Vitamin Dmentioning
confidence: 99%
“…In this sense, it has been shown that the prevalence of vitamin D deficiency increases among older children [39,40], and puberty seems to influence this deficiency [4,41], probably due to the increased requirement of vitamin D for growth and bone turnover [14]. It is worth noting that puberty is marked by an increase in body weight, which is associated with IR and a reduction in serum 25(OH)D levels [17,[41][42][43]. However, previous studies found no associations between serum 25(OH)D and insulin parameters in prepubertal children [38,42].…”
Section: Puberty Insulin Resistance and Vitamin Dmentioning
confidence: 99%
“…(1) the case group met the diagnostic criteria of girls' precocious puberty, i.e., girls presented with secondary sexual signs at < 8 years old (Tanner stage ≥ II) or menarche at < 10 years old, or boys presented with secondary sexual signs at < 9 years old (17); and (2) girls or boys in the control group met the screening criteria of normal weight or obesity of girls or boys without precocious puberty aged 6-10 years. According to the Group of China Obesity Task Force BMI cutoff-point standard for obesity screening of girls aged 2-18 years old, the BMI of obese girls aged 7, 8, 9 years old is 18.8, 19.5, 20.4 kg/m 2 , the BMI of obese boys aged 7, 8, 9, 10 years old is 19.2, 20.1, 21.1, and 22.2 kg/m 2 , respectively (18).…”
Section: Study Objects and Population Samplingmentioning
confidence: 99%
“…Hispanics showed no significant differences in timing of puberty respect to weight while African American showed a trend of late puberty in obese [ 129 ]. Different results may be recorded depending on the observed population [ 137 , 138 ]. Finally, it is important to underline the effect of concomitant insulin resistance on pubertal development, which it’s not completely elucidated.…”
Section: Exogenous Causesmentioning
confidence: 99%